Maori Public Policy: Needs rights and the Politics of Indigeneity - O'Sullivan, Dominic (APSA, 2007)
In 2004 the appointment of a Coordinating Minister Race Relations, signalled a shift in elite Maori policy thinking from a long-standing cautious bipartisan acceptance of self-determination towards a re-emergent assimilationist 'one law' for all discourse. The question simplistically posed by the Leader of the Opposition was should welfare entitlements be granted on the basis of need or race? (Brash 2004). Beneath this question lies an ideological assumption which privileges assimilation over indigeneity as the basis of Maori participation in public affairs. This paper therefore asks: are Maori peoples with rights, or individuals with needs? Is there a deeper politics of indigeneity providing a legitimate foundation for rights which are not necessarily superior to the rights of citizenship, but are important and distinguishable adjuncts? These questions transcend the issue of welfare entitlements to wider questions about the nature and terms of Maori belonging to the liberal polity. The paper highlights the political tension between government attempts to remove indigeneity from the public agenda in response to populist pressure and a pragmatic acceptance that New Zealand 'needs' Maori to increase their contribution to the national economy and that the realisation of this goal may in fact depend on the fuller citizenship imagined by the politics of indigeneity.
Keywords: Maori Politics; New Zealand Politics

The Politics of Indigeneity and contemporary challenges to Maori self-determination - O'Sullivan, Dominic (Australasian Political Studies Association Conference, 2004)
Keywords: Populist; Self-Determination; Treaty of Waitangi

Philosophical Foundations of Maori-Crown Relations in the Twenty First Century: Biculturalism or Self-Determination - O'Sullivan, Dominic (Australasian Political Studies Association Conference, 2003)
This paper demonstrates that the philosophical premises underlying biculturalism and self-determination lead to different conclusions about where power properly resides with respect to Crown/Maori relations in New Zealand. It is argued that biculturalism is not the panacea for the realisation of legitimate Maori aspirations that has been assumed by both Maori and Pakeha policy elites over the past twenty years because it makes assumptions about power relationships which limit greater degrees of Maori autonomy ' one step towards self-determination is permitted, but the next prevented. Biculturalism can not realise greater autonomy because it is concerned primarily with relationships among people in institutional settings and within and among bureaucratic institutions. Therefore it is less likely to meet Maori aspirations than self-determination which is concerned with creating, to the greatest extent possible, independence and autonomy for groups, not necessarily in isolation from wider society, but certainly apart from controls and regulations imposed from outside the would be self-determining community. Self-determination locates power, at least to some extent, within traditional Maori social units, while biculturalism, although assuming a sharing of power, inevitably gives Maori the status of junior partner in a project designed to modify state institutions to make them more responsive to Maori interests. While in itself this is advantageous to Maori, biculturalism is not a substitute for the affirmation of traditional social structures as the central point in a Maori quest for greater independence from an historically intrusive state.
Place: Australia
Keywords: Biculturalism; Indigenous Politics; Maori; New Zealand Politics; Self-Determination

A Conversation About Kaupapa Māori Theory and Research - Pihama, L (2011)

Restoring the Nation: Removing the Constancy of Terror - Jackson, Moana (TRADITIONAL KNOWLEDGE CONFERENCE 2008 TE TATAU POUNAMU: THE GREENSTONE DOOR, 2008)

Nation building & Māori development in the 21st century: conference proceedings, 30th August to 1st September 2000. - University of Waikato School of Māori and Pacific Development (School of Māori and Pacific Development, The University of Waikato, 2001)
Keywords: economic conditions; government; māori development; self-determination; sovereignty

The Māori seats in Parliament - Joseph, Philip (New Zealand Business Roundtable, 2008)
The Māori seats in Parliament / Philip A. Joseph.-book

Partnerships toward the realization of the right to self-determination - Charters, Claire (2022)

‘The Quid Pro Quo’: Why did the Crown decide to settle Māori historical treaty claims? - McDowell, Tiopira (2016)
Between 1991 and 1994, Minister in Charge of Treaty of Waitangi Negotiations Douglas Graham and the recently established Treaty of Waitangi Policy Unit developed a series of policy proposals that outlined an ambitious plan to settle Māori historical treaty claims. These papers were refined via extensive consultation and discussion with Cabinet Ministers and government officials: Māori as treaty partner were not consulted. In late 1994 the proposed policy was approved by Cabinet and published as Crown Proposals for the Settlement of Treaty of Waitangi Claims. Why did the Crown decide to settle Māori historical treaty claims in the early 1990s? What did it expect to gain from settling treaty claims? Why, after nearly a century and a half of relative complacency, and nearly two decades after the establishment of the Waitangi Tribunal to hear and make recommendations on Māori grievances, was the Crown suddenly prompted into action? And why would a right wing National government with little support from Māori voters and few current or previous Māori MPs launch a treaty claims settlement policy that would greatly antagonize its traditional voting base? These questions will be addressed via an examination of Cabinet papers, policy documents, legislation, deeds of settlement, published accounts and interviews with some of the key players. It will be argued that the treaty claims settlement policy was initiated as a consequence of New Zealand Māori Council v Attorney-General 1987, popularly known as the Lands case, and developed to achieve three specific outcomes: diversion of claimants away from the Waitangi Tribunal, containment of the financial risks posed by the Tribunal’s newly found binding and resumptive powers, and a progressive ‘winding back’ of Māori rights and Crown obligations embedded in legislation.
Keywords: crown policy; kāwanatanga; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Seabed and foreshore: How politics impacts upon the sustainability of a resource - Mulholland, Malcolm (2005)
Keywords: can't find source - further research required

Contested Realities: Race, Gender and Public Policy in Aotearoa/New Zealand - McIntosh, Tracey (2001)
Keywords: discrimination; mana wāhine